Preparation of a Growth Hormone Receptor/Prolactin Receptor Bispecific Antibody Antagonist Which Exhibited Anti-Cancer Activity - Xin Chen; Di Wu; Yan Zheng; Xingxing Liu; Jianmeng Wang (Frontiers Media S.A., 2020)
Prolactin receptor (PRLR) and growth hormone receptor (GHR) are closely related to the occurrence and development of breast cancer, and breast cancer cell endogenously express GHR, PRLR and GHR-PRLR heterodimer. In this case, the combined use of PRLR or GHR inhibitors may produce better anti-breast cancer potential than PRLR or GHR inhibitors alone. In this case, it is necessary to develop the dual-function GHR/PRLR antagonists with anti-breast cancer potential. For this, we used hybridoma technology to generate an anti-idiotypic antibody (termed H53). We then used various techniques, including competitive ELISA, competitive receptor binding analysis, and indirect immunofluorescence assay to identify H53, and the results show that H53 behaves as a typical internal image anti-idiotypic antibody (Ab2β). Further experiments indicate that H53 is a dual-function inhibitor, which not only inhibited PRLR-mediated intracellular signaling, but also blocked GHR-mediated intracellular signaling in a dose-dependent manner. Furthermore, H53 could inhibit PRL/GH-driven cancer cell proliferation in vivo and in vitro. This study indicates that H53 exhibits potential biological activity against breast tumors, which implies that internal image anti-idiotypic antibodies may be a useful strategy for the development of PRLR/GHR dual-function antagonists for breast cancer therapy.